2003
DOI: 10.1002/hipo.10121
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of granule cell dendrites after mossy fiber arrival in hippocampal field CA3

Abstract: Most granule neurons in the rat dentate gyrus are born over the course of the first 2 postnatal weeks. The resulting heterogeneity has made it difficult to define the relationship between dendritic and axonal maturation and to delineate a time course for the morphological development of the oldest granule neurons. By depositing crystals of the fluorescent label Dil in hippocampal field CA3, we retrogradely labeled granule neurons in fixed tissue slices from rats aged 2-9 days. The results showed that all label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 61 publications
(96 reference statements)
9
75
1
Order By: Relevance
“…Thus, they showed that from the superficial granule cells, several dendrites, including apical and basal dendrites, grow into the surrounding neuropil, and that these dendrites have the classical appearance of growing dendrites, including lamellipodia and filopodia as described previously (Seress and Pokorny, 1981;Lubbers and Frotscher, 1988). It was also shown that the basal dendrites regress because they are a transient feature of granule cells during their development and adult rodent granule cells never display basal dendrites (Jones et al, 2003). Consistent with previous developmental studies, dendritic arbors become pruned to form only a few apical dendrites that branch in regular ways in the molecular layer Desmond and Levy, 1984;Green and Juraska, 1985;Rihn and Claiborne, 1990).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Thus, they showed that from the superficial granule cells, several dendrites, including apical and basal dendrites, grow into the surrounding neuropil, and that these dendrites have the classical appearance of growing dendrites, including lamellipodia and filopodia as described previously (Seress and Pokorny, 1981;Lubbers and Frotscher, 1988). It was also shown that the basal dendrites regress because they are a transient feature of granule cells during their development and adult rodent granule cells never display basal dendrites (Jones et al, 2003). Consistent with previous developmental studies, dendritic arbors become pruned to form only a few apical dendrites that branch in regular ways in the molecular layer Desmond and Levy, 1984;Green and Juraska, 1985;Rihn and Claiborne, 1990).…”
Section: Introductionsupporting
confidence: 54%
“…Also, they showed that in all regions of the dentate gyrus, the more superficial neurons in the granule cell layer are formed earlier than the deeper granule cells. In the early postnatal dentate gyrus, Jones et al (2003) have described a multipolar morphology for the developing dendrites of granule cells. Thus, they showed that from the superficial granule cells, several dendrites, including apical and basal dendrites, grow into the surrounding neuropil, and that these dendrites have the classical appearance of growing dendrites, including lamellipodia and filopodia as described previously (Seress and Pokorny, 1981;Lubbers and Frotscher, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, 4-week-old granule cells are generally considered to be functionally mature (Markakis and Gage, 1999;Liu et al, 2000;Jones et al, 2003;Ambrogini et al, 2004;Espó sito et al, 2005;OverstreetWadiche et al, 2006a;Zhao et al, 2006). GFP expression in these animals therefore provides an efficient means to examine the morphology of mature hippocampal dentate granule cells.…”
Section: Gfp-expressing Neurons (0 Of 832 Cells)mentioning
confidence: 99%
“…In addition, it needs to migrate, mature, and establish presynaptic and postsynaptic connections. In the developing hippocampus, this process has been studied extensively (Lübbers and Frotscher, 1988;Laurie et al, 1992;Super and Soriano, 1994;Tyzio et al, 1999;Hennou et al, 2002;Gozlan and Ben Ari, 2003;Jones et al, 2003), but the sequence of events leading to neuronal maturation in the adult hippocampus remains unknown. Given the differences in the developing and adult environments, the process of maturation and the factors that modulate it may also differ.…”
Section: Introductionmentioning
confidence: 99%